2020
DOI: 10.1111/ejss.13053
|View full text |Cite
|
Sign up to set email alerts
|

Slippery liquid‐infused porous surfaces: The effect of oil on the water repellence of hydrophobic and superhydrophobic soils

Abstract: Soil wettability is important for understanding a wide range of earth system processes, from agricultural productivity to debris flows and sediment fan formation. However, there is limited research considering how soil–water interactions, where the soil grains are naturally hydrophobic, might change in the presence of oil from natural hydrocarbon leakage or oil spills. Here we show how slippery liquid‐infused porous surfaces (SLIPS) apply to hydrophobic soils, by physical modelling of surfaces of different gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 101 publications
(144 reference statements)
0
7
0
Order By: Relevance
“…For any pair of the droplet More details on SLIPS preparation can be found elsewhere. 28,50 For droplets, two series of liquids were used. The first series of liquids was a set of homologous alkanes (purity 99%, Sigma Aldrich) including Pentane (C5H12), Hexane (C6H14), Heptane (C7H16),…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For any pair of the droplet More details on SLIPS preparation can be found elsewhere. 28,50 For droplets, two series of liquids were used. The first series of liquids was a set of homologous alkanes (purity 99%, Sigma Aldrich) including Pentane (C5H12), Hexane (C6H14), Heptane (C7H16),…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Edible infused-liquids included olive and avocado oils (Sainsbury’s UK) and C8-MCT oil (Wellgard). More details on SLIPS preparation can be found elsewhere. , …”
Section: Experimental Methodsmentioning
confidence: 99%
“…binarisation of images, placement of baseline, identification of points along the drop profile) in comparison to the approach used in this work. McCerery et al [50]have used the open source program PyDSA to detect the baseline and the drop profile and fit an ellipse to determine the contact angle. This algorithm, however, uses the reflection of the sessile drop to determine both the placement of the baseline and subsequently the tangent to the drop profile and might therefore not be appropriate for the case where the sessile drop is deposited on a granular, non-reflective surface.…”
Section: Measuring the Contact Angle In The Macro-scale: The Sessile ...mentioning
confidence: 99%
“…[Color figure can be viewed at wileyonlinelibrary.com] discovered outside of the oil sands region, indicating even more widespread glacial transport. Rutherford (1928) Previous work on the physics of sediment surfaces has shown that oils, such as those found in the AOS, alter the surface chemistry of individual particles-creating a hydrophobic (water repellent) sediment with very limited water infiltration (Gordon et al, 2018;McCerery et al, 2021). The presence of an oil in sediments can also create thin lubricant coatings on the particles that allow for enhanced water shedding, making the sediment 'slippery ' (McCerery et al, 2021).…”
mentioning
confidence: 99%
“…Rutherford (1928) Previous work on the physics of sediment surfaces has shown that oils, such as those found in the AOS, alter the surface chemistry of individual particles-creating a hydrophobic (water repellent) sediment with very limited water infiltration (Gordon et al, 2018;McCerery et al, 2021). The presence of an oil in sediments can also create thin lubricant coatings on the particles that allow for enhanced water shedding, making the sediment 'slippery ' (McCerery et al, 2021). For this to occur, several other conditions must be met in the sediment system: (i) the primary sediment must be fine-grained (clay-fine sand sized), (ii) the sediment chemistry must preferentially wet one of the lubricants/ liquids and (iii) sufficient water delivery is required to sustain lubrication.…”
mentioning
confidence: 99%